PENGARUH ANALISIS JABATAN DAN BEBAN KERJA TERHADAP PRODUKTIVITAS KERJA PADA PEGAWAI DINAS KESEHATAN KOTA METRO LAMPUNG - Hasan, Verdalena; Sigalingging, Marhaban; Widodo, Deny Edy (Universitas Muhammadiyah Metro, 2025)
This study uses associative descriptive designs and the population is all the ASN staff who work in the Metro City Health Service of 76 people, whereas the Sampling technique in this study is with saturated sampling is a sample determination technique when all members of the population are used as samples. Then the determination of the minimum number of samples in this study based on the calculation as obtained of 55 respondents. Data collection using a Google form questionnaire lift and data analysis using double linear regression with interpretation of partial test t, simultaneous f, and determinant coefficients. Analysis results show that 1) job analysis is an important tool for increasing work productivity. By conducting job analysis consistently and effectively, organizations can put the right employees in place, improve performance, and create a positive work culture. 2) The right workload can have a positive impact on work productiveness, but excessive workloads can have negative consequences. 3) Effectively performed post analysis and workload is an important tool for increasing the productivity of work in the Metro City Health Service Office. By applying the aspects in the previous discussion, the Metro Health Service can create an enabling working environment for its employees to work productively and optimally, thus resulting in improved quality of health services for the public. Advice 1) Good post analysis is an important tool to help the organization its goals. With accurate and complete information about the assignment, organizations can make more appropriate decisions in terms of human resource management, which will ultimately have a positive impact on the performance and success of organizations already showing optimal results and need to beined. 2) The complexity of the job given to an employee is at an ideal level. This means that the employee has enough challenges to stay motivated and productive, but not too much to cause stress or fatigue, then the need is evaluated by the leader. It shows that the staff has excellent performance and makes a significant contribution to the organization, so it is necessary to maintain.